The [α/Fe]-[Fe/H] relation in the E-MOSAICS simulations: its connection to the birth place of globular clusters and the fraction of globular cluster field stars in the bulge - Hughes, Meghan E.; Pfeffer, Joel L.; Martig, Marie; Reina-Campos, Marta; Bastian, Nate; Crain, Robert A.; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2020)
The α-element abundances of the globular cluster (GC) and field star populations of galaxies encode information about the formation of each of these components. We use the E-MOSAICS cosmological simulations of ∼L* galaxies and their GCs to investigate the [α/Fe]–[Fe/H] distribution of field stars and GCs in 25 Milky Way–mass galaxies. The [α/Fe]–[Fe/H] distribution of GCs largely follows that of the field stars and can also therefore be used as tracers of the [α/Fe]–[Fe/H] evolution of the galaxy.